An analysis of resistance training based on the maintenance of mechanical power - Legaz Arrese, A.; Reverter-Masia, J.; Munguia Izquierdo, D.; Ceballos-Gurrola, O. C. (The Journal of Sports Medicine and Physical Fitness, 2007)
Resistance training techniques, that increase the global power output of an exercise, exercise set and continuous sets, can optimize neuromuscular adaptation and dynamic athletic performance. An observation that is apparent during traditional resistance training is the slowing of movement velocity as fatigue increases. To perform at maximum velocity, only repetitions that permit maintenance of the maximum power output are essential for increasing the global power output. This article reviews the available research which examines the pattern of velocity decrease with different load intensities. In addition, an analysis is performed of the possible advantages of resistance training based on the maintenance of the mechanical power versus traditional resistance training. Furthermore, a variety of fact-finding lines are proposed with the objective of answering the numerous open questions related to resistance training based on the maintenance of mechanical power